Knowledge and the family firm through generations: a knowledge-based approach in various geographic contexts - Duarte Alonso, Abel; Kok, S. (TAYLOR & FRANCIS LTD, 2020)
This study examines the significance of knowledge, how it is created, and more specifically, its evolution and beneficial changes to the firm through the generational process from the perspective of the knowledge-based view (KBV) of the firm. Drawing from this theory, and its associations with the study’s findings, a theoretical framework is proposed to enhance the understanding of knowledge in the context of family firms’ generational processes. The study draws from data gathered among five family firms operating in both Northern and Southern Hemispheres. Overall, knowledge was created through previous experiences, accumulation of and conversion of explicit knowledge into tacit knowledge. The benefits of knowledge accumulation and sharing were multiple, including through efficiencies, new product development, or building business resilience. These findings also were associated with the KBV of the firm, for instance, in the added value added that stems from knowledge creation and operationalisation, particularly through tacit knowledge.